1995
DOI: 10.1021/ja00112a001
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic, Non-Hydrogen-Bonding Bases and Base Pairs in DNA

Abstract: We report the properties of hydrophobic isosteres of pyrimidines and purines in synthetic DNA duplexes. Phenyl nucleosides 1 and 2 are nonpolar isosteres of the natural thymidine nucleoside, and indole nucleoside 3 is an analog of the complementary purine 2-aminodeoxyadenosine. The nucleosides were incorporated into synthetic oligodeoxynucleotides and were paired against each other and against the natural bases. Thermal denaturation experiments were used to measure the stabilities of the duplexes at neutral pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
195
0
15

Year Published

1998
1998
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 266 publications
(221 citation statements)
references
References 39 publications
11
195
0
15
Order By: Relevance
“…Compound 2 crystallized readily during the reaction and was easily isolated and purified. Tritylation of 2 with 1.5-equivalent of 4,4′-dimethoxytrityl chloride partially protected both the 5′-and 3′-hydroxyl groups of the sugar as revealed by 1 H-NMR spectrum of the isolated main product (not shown), although such procedure performed on other modified bases protected only the 5′-hydroxyl group [10,15,16,20,22]. Therefore, only 1.1-equivalent of 4,4′-dimethoxytrityl chloride was used for the reaction and a 75% yield for 3 was achieved after chromatography purification.…”
Section: Synthesis Of 1'-(7-azaindolyl)-2'-deoxy-d-riboside and Its Cmentioning
confidence: 97%
See 2 more Smart Citations
“…Compound 2 crystallized readily during the reaction and was easily isolated and purified. Tritylation of 2 with 1.5-equivalent of 4,4′-dimethoxytrityl chloride partially protected both the 5′-and 3′-hydroxyl groups of the sugar as revealed by 1 H-NMR spectrum of the isolated main product (not shown), although such procedure performed on other modified bases protected only the 5′-hydroxyl group [10,15,16,20,22]. Therefore, only 1.1-equivalent of 4,4′-dimethoxytrityl chloride was used for the reaction and a 75% yield for 3 was achieved after chromatography purification.…”
Section: Synthesis Of 1'-(7-azaindolyl)-2'-deoxy-d-riboside and Its Cmentioning
confidence: 97%
“…There are mainly two groups of 'bases' synthesized and incorporated into DNA oligomers: those made by minor modification of the natural bases or the derivatives of cyclic aromatic compounds. While the former includes 2-aminopurine [1][2][3][4][5][6][7][8], inosine [9] and isoinosine [9][10][11], 3-and 7-deazaadenine [12][13][14][15], and 3-and 7-deazaguanine [14,16], the latter includes analogs of pteridine [17][18][19] and indole [20][21][22][23][24], benzene [23][24][25][26], naphthalene and pyrene derivatives [24], The first group of compounds, when replacing a natural base in duplex DNA, can still form hydrogen bonds with the base in the opposite strand, while the second group of compounds cannot form any hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporation of a phenyl residue in place of C4 in the r(CCCCGGGG) octamer leads to loss of WatsonCrick hydrogen bonds and goes along with changes in intra-and interstrand stacking interactions and hydration+ A comparison of the thermodynamics of duplex formation for the native RNA and two modified octamers containing a single phenyl at either position 2 or 4 is given in Table 1+ Accordingly, incorporation of the phenyl moiety leads to a drastic loss in stability in both cases+ The changes of around ϩ25 kcal/mol in the enthalpy term for duplex formation are consistent with unfavorable stacking interactions and absence of Watson-Crick hydrogen bonds between phenyls and between phenyl and guanine in the [r(CCCPGGGG)] 2 and [r(CPCCGGGG)] 2 duplexes, respectively+ However, formation of the modified duplexes goes along with favorable entropic contributions relative to the native RNA octamer+ Inspection of the structure reveals that there is no overlap between phenyls and 59-cytosines and that the dispersive contributions to stacking between phenyls and 39-guanines are probably rather limited+ As shown in Figures 2B and 3B, the lack of exocyclic functions with phenyl allows only for van der Waals contacts between the C2-C3 and N7-C8 edges of P and G, (Schweitzer & Kool, 1995;reviewed in Turner, 1996)+ Our structure suggests that hydrophobic residues may exhibit a similar selectivity in the case of RNA+ It is likely that the shift between strands that generates the P-P pair is further facilitated by the formation of 39-terminal unpaired guanines (Figs+ 1B, 4A,B)+ Among the possible dangling-end arrangements involving natural bases, 39-terminal purines afford the greatest stability, followed by 39-terminal pyrimidines and 59-terminal purines (Petersheim & Turner, 1983;Sugimoto et al+, 1987)+ Using hexose-oligonucleotide analogs, Eschenmoser and coworkers demonstrated that the different stabilities provided by 59-and 39-overhanging residues are correlated with the degree of inclination between backbone and bases (Micura et al+, 1999)+ Similarly, the base-backbone inclination present in natural RNA duplexes leads to more optimal intraand interstrand stacking interactions between a 39-terminal unpaired base and an adjacent base pair (Fig+ 1B, right) compared to the corresponding situation for a 59-overhanging base+…”
Section: Structure and Stabilitymentioning
confidence: 99%
“…A: Preparation of 1-Deoxy-1-phenyl-b-D-ribofuranose derivative suitable for oligonucleotide synthesis; compound 5 corresponds to the phenyl ribonucleoside+ Reagents: i: Triflic acid, benzyl 2,2,2-trichloroacetimidate; ii: Phenyllithium; Ϫ78 8C; iii: Triethylsilane, boron trifluoride etherate, Ϫ40 8C; iv: Boron tribromide, Ϫ78 8C; v: 4,49-Dimethoxytrityl chloride, pyridine; vi: Silver nitrate, t-butyldimethylsilyl chloride, tetrahydrofuran/pyridine; vii: 5% Triethylamine in methanol; viii: 2-Cyanoethyl N,N-diisopropylchlorophosphoramidite, N-methylimidazole, N,N-diisopropylethylamine+ B: Possible structures for single-and double-stranded arrangements of the RNA octamer CCCPGGGG+ Cytosines are drawn as open boxes, guanines are dashed, and phenyls are black+ From left to right: duplex with two P-G mismatches; hairpin with three C-G base pairs in the stem and a P-G loop; duplex with a central purine-purine base pair and loopedout Ps; duplex with strands slid along each other by one base-pair step, generating a central P-P pair and 3-terminal G overhangs+ The arrangement on the far right is observed in the crystal structure+ 9 with phenyl decreased the catalytic rate only 20-fold compared to the 2,000-fold deleterious effect resulting from removal of the adenine base+ Another surprising observation was the almost wild-type activity of a nuclear pre-mRNA variant with an adenine r phenyl mutation at the 39-splice AG during the second step of the splicing reaction (Gaur et al+, 2000)+ The consequences of hydrophobic, non-hydrogenbonding bases and base pairs for duplex stability and nucleic acid-protein interactions have been investigated in some detail with DNA but remain largely unexplored in the case of RNA+ Thus, difluorotoluene (F), a nonpolar analog of thymine codes specifically for adenine replication (Moran et al+, 1997) and the geometry of the F-A pair closely resembles that of T-A, although F causes destabilization of the DNA duplex (Guckian et al+, 1998)+ Similarly, a pyrene nucleoside analog shows significant selectivity for a model abasic site over the natural bases (Matray & Kool, 1998) and polymerases efficiently incorporate the pyrene residue opposite a template site lacking a base (Matray & Kool, 1999)+ In DNA duplexes, nonpolar isosteres of adenine and thymine pair with a stability that is similar to that of the T-G mismatch base pair (Schweitzer & Kool, 1995)+ Moreover, at the ends of helices such hydrophobic pairs can be more stabilizing than a canonical A-T pair and, interestingly, hydrophobic analogs prefer to pair with a hydrophobic partner rather than a natural base+ Attached at the 59-terminus of a DNA duplex as single dangling nucleotides, nonpolar aromatic analogs were found to be equally or more stabilizing than the four natural bases (Guckian et al+, 2000)+ Here, we report a new chemical synthetic route for preparing the phenyl ribonucleotide+ To shed light on the energetic and structural consequences of the incorporation of the phenyl nucleotide analog into an RNA duplex, we analyzed the thermodynamic stability of RNA octamers with single phenyl residues (P) and determined the crystal structure of r(CCCPGGGG)+ The structure gives the first detailed picture of the interactions of the hydrophobic phenyl nucleotide in the context of an RNA duplex and may aid in the rationalization of the accumulated activity data for RNAs bearing the phenyl modification+…”
Section: Introductionmentioning
confidence: 99%